Pengaruh Kedisiplinan Dan Fasilitas Belajar Terhadap Prestasi Belajar Siswa Kelas Tinggi Sd Negeri Gumpang 01 Kartasura Tahun Pelajaran 2015/2016 - ARIFIANTI, ERVIN (2016)
ABSTRACT Evin Arifianti/A 510120046. THE INFLUENCE OF DISCIPLINE AND FACILITIES LEARN TO STUDENT LEARNING ACHIEVEMENTS HIGH CLASS PUBLIC GUMPANG 01 KARTASURA YEARS LESSONS 2015/2016. Research Paper. The Teaching and Science Education, Muhammadiyah University Surakarta. January, 2016. Factors affecting the learning achievement, praying only is discipline. That lie can be a factor affecting student learning achievement is already used to learn. The aims of this study is to find: (1) Determine the influence achievement learn discipline Against High Grade Elementary School Students Gumpang 01 Kartasura Academic Year 2015/2016. (2) Determine the influence has been used to learn Against Higher Learning achievement Elementary School Students Gumpang 01 Kartasura Academic Year 2015/2016. (3) Determine the influence of discipline and has been used to learn Against High Grade Student Achievement Elementary School Gumpang 01 Kartasura Academic Year 2015/2016. This research includes quantitative research. The population in this study were 145 high-grade primary school students Gumpang 01 Kartasura. The sample in this study were 60 students of high grade. Data collection techniques in this study was a questionnaire and documentation. Data analysis technique used is multiple linear regression analysis, t test, F test, the coefficient of determination, SR and SE. Based on the results of multiple linear regression equation Y = 37.012 + 0.237 X1 + 0.261 X2. The results of data analysis the significance level of 0.05 was obtained: (1) There is a disciplinary effect on learning achievement. This is based on test results t is known that tcount> ttable, namely 2.229> 2.002 and the significance value <0.05 (0.030 <0.05). (2) There is an effect on the learning achievement of learning facilities. This is based on test results t is known that tcount> ttable, namely 2.109> 2.002 and the significance value <0.05 (0.039 <0.05. (3) There is an effect discipline and learning facilities to learning achievement. It is based on test F known that Fcount> Ftable is 13.821> 3.15 and a significance value <0.05 is 0.000. Key words: facilities learning , discipline and learning achievements